A numerical definition-based systematic design approach for coupling consumers ' image perception with product form. Issue 1 (7th March 2016) - Chen, Hung-Yuan; Chang, Yu-Ming; Chang, Hua-Cheng
Abstract : Purpose: – This paper aims to propose a numerical definition-based systematic design approach (NDSDA) to generate an explicit numerical definition of the product form profile and to establish the correlation between the product form features and the corresponding consumers' image perceptions. Design/methodology/approach: – To illustrate the feasibility of the proposed method, this study considers the design of a two-dimensional automobile profile for illustration purposes and commences by developing a detailed numerical definition of an automobile profile using Bézier curves. A series of automobile image evaluations are conducted to examine the relationship between the characteristics of an automobile profile and its associated consumer image perception. Finally, the evaluation results are analyzed statistically, and the statistical results are used to construct mathematical models formalizing the correlations between the automobile profile design variables and the consumers' perceptions of the product image. Findings: – The results of the evaluation trials are used to construct mathematical models capable of predicting the likely consumer response to any automobile profile designed in accordance with the numerical definition. Furthermore, the evaluation data enable the critical design variables and form features to be determined such that the efficacy of the design process in creating automobiles which better meet the consumers' image aspirations can be improved. Originality/value: – The major contribution of the NDSDA methodology presented in this study is the ability it gives to designers to specify the product form in a detailed yet highly efficient manner. Furthermore, the numerical definition of the product form not only provides a suitable basis for identifying the critical design variables and form features of the product but also provides an understanding of how these variables should be manipulated to obtain or reinforce the desired product image.